Estrogenic regulation of testicular expression of stem cell factor and c-kit: implications in germ cell survival and male fertility - Correia, Sara (2014)
Objective: To study the effect of estrogens regulating the testicular expression of stem cell factor (SCF) and c-kit. Design: Experimental study. Setting: University research center. Animal(s): Male Wistar rats. Intervention(s): Rat seminiferous tubules (SeT) cultured in the presence or absence of 17β-estradiol (E2). Main outcome measure(s): Expression of SCF and c-kit as well as apoptotic factors, FasL, FasR, Bcl-2, and Bax analyzed via quantitative reverse transcription-polymerase and Western blot; enzymatic activity of apoptosis effector caspase-3 assessed by colorimetric assay; proliferation index in SeT epithelium determined via fluorescent immunohistochemistry of nuclear proliferation marker Ki67. Result(s): E2 (100 nM) induced a decrease in c-kit expression while increasing expression of SCF. Altered expression of the SCF/c-kit system relied on apoptosis of germ cells, as evidenced by the up-regulated expression of FasL/FasR, the increased ratio of proapoptotic/antiapoptotic proteins (Bax/Bcl-2), and the augmented activity of caspase-3. Decreased proliferation was also found in SeT in response to E2. Conclusion(s): A 100 nM dose of E2 unbalance the SCF/c-kit system, with a crucial impact on germ cell survival and thus male fertility. These findings contribute to our knowledge of the mechanisms underlying male idiopathic infertility associated with hyperestrogenism and open new perspectives on treatment targeting estrogen-signaling mechanisms.